Acute Exposure to Microcystin-Producing Cyanobacterium Microcystis aeruginosa Alters Adult Zebrafish (Danio rerio) Swimming Performance Parameters - Luiza Wilges Kist; Angelo Luis Piato; João Gabriel Santos da Rosa; Gessi Koakoski; Leonardo José Gil Barcellos; João Sarkis Yunes; Carla Denise Bonan; Maurício Reis Bogo (Journal of Toxicology)
Microcystins (MCs) are toxins produced by cyanobacteria (blue-green algae), primarily Microcystis aeruginosa, forming water blooms worldwide. When an organism is exposed to environmental perturbations, alterations in normal behavioral patterns occur. Behavioral repertoire represents the consequence of a diversity of physiological and biochemical alterations. In this study, we assessed behavioral patterns and whole-body cortisol levels of adult zebrafish (Danio rerio) exposed to cell culture of the microcystin-producing cyanobacterium M. aeruginosa (MC-LR, strain RST9501). MC-LR exposure (100 μg/L) decreased by 63% the distance traveled and increased threefold the immobility time when compared to the control group. Interestingly, no significant alterations in the number of line crossings were found at the same MC-LR concentration and time of exposure. When animals were exposed to 50 and 100 μg/L, MC-LR promoted a significant increase (around 93%) in the time spent in the bottom portion of the tank, suggesting an anxiogenic effect. The results also showed that none of the MC-LR concentrations tested promoted significant alterations in absolute turn angle, path efficiency, social behavior, or whole-body cortisol level. These findings indicate that behavior is susceptible to MC-LR exposure and provide evidence for a better understanding of the ecological consequences of toxic algal blooms.